THERMAL PROTECTION OF ROADS IN THE PERMAFROST ZONE - Galkin, Aleksandr; Pankov, V. Yu. (Journal of Applied Engineering Science, 2022)
The problem of choosing a method of construction of thermal protection layer of the road pavement in permafrost zone was solved. Simple engineering formulas to justify the choice of the specific type of thermal insulation structure were obtained. It was determined that a structure composed of two layers (separate layers insulant and of sand) is always more efficient than a thermal insulation mixture (combined insulant and sand) applied in one layer for the purposes of maximizing thermal resistance. At the same time, a quantitative assessment demonstrated that in many practical cases, the difference in thermal resistance of the two kinds of structures is slight and is within the margins of permissible precision of engineering calculations. For this reason, it is expedient to also consider the technological demands of application of one or the other type of thermal insulation layer in addition to the thermal resistance considerations. Formulas to find the area of rational use of thermal insulation mixtures instead of merely sand bedding were devised. It was determined that the thickness of bedding in one or the other case is significantly dependent on the ratio of thermal conductivity coefficients of sand and the insulant. In addition, the change in relative thickness of the layer can have both negative and positive values.
Keywords: temperature, thermal conductivity, mixtures, structural design, permafrost zone, road pavement, thermal insulation, thermal resistance, energy efficiency, foam glass aggregate